Theorising craft practices through sketching: The case of Swedish post-compulsory floristry and textile education - Gåfvels, Camilla; Lindberg, Viveca (FormAkademisk, 2021)
This article explores how craft practice is theorised through sketching, by comparing narratives about the role of sketching from interviewed Swedish upper secondary textile design and floristry education teachers, and aiming to discern connection to curriculum. The theory and methods used in the article are influenced by Ivor Goodson’s work on subject knowledge and curriculum change (1998). Empirical data was obtained from multiple sources, including interviews with four teachers. The findings reveal that, while sketching has been intrinsic to textile design and seamstress vocational knowing for considerable time, sketching is a relatively new phenomenon within floristry vocational knowing and education; essentially dating from the 2011 Swedish educational reform. The discussion claims that sketching provides means to theorise craft practice, through providing an intermediary level between the abstract (theory) and the concrete (objects) within the practice